Taxonomic notes on Weissia subgenus Astomum, including Weissia wilsonii D.A.Callaghan, a new species from Europe. (3rd April 2019) - Callaghan, Des A.; Bell, Neil E.; Forrest, Laura L.
ABSTRACT: Introduction. The present study investigates the taxonomy of European members of Weissia Hedw. subgenus Astomum Hampe., a group considered taxonomically difficult and including species of high conservation concern. Methods. A broad set of samples were subject to DNA sequencing and morphological analysis, plus a review of type material was undertaken. Key Results and Conclusions. Three taxonomic additions and changes are supported. (1) Weissia longifolia var . angustifolia (Baumgartner) Crundw. & Nyholm is raised to species rank, W. angustifolia (Baumgartner) D.A.Callaghan, comb. et. stat. nov . (2) The type of W. multicapsularis (Sm.) Mitt. comprises an intermix of Phascum cuspidatum Hedw. and W. longifolia Mitt., and the protologue refers to unique features of P. cuspidatum but no such features of W. longifolia . Weissia multicapsularis is therefore described as a new synonym of P. cuspidatum . (3) Plants that have been named as W. multicapsularis by modern authors comprise an undescribed species, here named W. wilsonii D.A.Callaghan, sp. nov . An illustrated key to European species of Weissia subgenus Astomum is provided.